(untitled) (LEARNing Landscapes, 2014)
Scholarship on field experiences often addresses issues of integration with coursework and the development of students’ pedagogical knowledge, with less focus on their role in the development of teachers’ professional identities. Drawing on data from a yearlong qualitative study, this article addresses a central concern for students in a literacy teacher preparation program—fieldwork as a lonely venture. This research suggests that traditional field experiences explicitly and implicitly perpetuate images of teaching as a solitary act. These findings highlight the need to reconceptualize field experiences as sites of inquiry in order to disrupt narratives of isolation within teacher education.